The quality of joint auditing and its role in improving the effectiveness of the tax system (An applied study at the General Tax Authority) - Faisal, Alaa Hamid; Kadhim, Hayder Oudah; Al- Laban, Dhyaa Abdulrazaq Abduljabar (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to examine the academic pillars of both joint audit standards and the tax system, with an indication of the nature of the relationship between the two, to identify appropriate ways to improve the tax system in this way. Provide support to adapt to various climate changes and developments. Two basic assumptions have put forward, namely: (1) the General Tax Authority is likely to implement joint audits in a way that guarantees the required standards, (2) improving the effectiveness of the joint audit tax system and Helps increase revenue. The research sample of General Tax Authority employees is for 2019 data. Analytical tools were used to achieve the desired results from the research, as the results showed that tax enforcement and collection required an efficient and effective system that would improve revenue, encourage investment and Provides assistance in achieving the desired targets of state budget financing, and as a result, there is a strong link between the joint auditing and development of the tax system and tax revenue. Ability to conduct joint audits to effectively achieve desired goals.